Rapid visual screening of building for potential ground movement in Kalirejo, Kulonprogo, Yogyakarta - Sari, Sely Novita; Prastowo, Rizqi; Junaidi, Rahmad; Machmud, Amir (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
Landslides are the biggest threat in the Kalirejo area. The dynamics of land movements in the mountains often cause cracks and potentially collapse. Landslides due to land fractures caused building damage. This study aimed to analyze the condition of a simple building on the influence of land fracture. The method used was conducting a field survey of existing buildings in the Kalirejo area. The data of the surveys were the percentage of building damage and building categorization. From the results of the analysis, the percentages of buildings in the safe category were 78 buildings or 54.17%, the buildings of the unsafe category were 51 buildings or 35.42%, and buildings with the unsafe category were 15 buildings out of 144 surveyed building with the percentage of 10.42%. Based on the results of the analysis using the Rapid Visual Screening (RVS) method, 15 buildings with unsafe conditions need to be relocated because they do not use the minimum structure required for simple buildings while the 51 buildings with unsafe conditions, repairs must be made to the structure according to the minimum requirements of simple buildings